A case of systemic lupus erythematosus complicated by subclinical Cushing's syndrome: case report. (2nd January 2020) - Nakayama, Yoichi; Taura, Daisuke; Shibue, Kimitaka; Kuramoto, Nobuo; Mimori, Tsuneyo; Inagaki, Nobuya
Abstract: An 18-year-old female was diagnosed with subclinical Cushing's syndrome (CS) due to a left adrenal adenoma. When she was 20 years old, she developed lupus nephritis. She was treated with high-dose prednisolone (PSL) and soon developed the symptoms of CS. When she was 25 years old, we evaluated her serum glucocorticoid level while she continued to take oral PSL. The result suggested her CS was affected by both the oral PSL and the endogenous cortisol secreted by the adrenocortical adenoma, which was therefore resected. Seven months after the operation, the patient's body weight was decreasing, and her SLE remained in clinical remission. CS complicated by SLE is rare, and the decision to surgically remove an adrenal tumor in such a case is even more rare.